Axotomy increases NADPH-diaphorase activity in the dorsal root ganglia and lumbar spinal cord of the turtle Trachemys dorbigni - W.A. Partata; A.M.R. Krepsky; M. Marques; M. Achaval (Brazilian Journal of Medical and Biological Research, 1999)
Seven days after transection of the sciatic nerve NADPH-diaphorase activity increased in the small and medium neurons of the dorsal root ganglia of the turtle. However, this increase was observed only in medium neurons for up to 90 days. At this time a bilateral increase of NADPH-diaphorase staining was observed in all areas and neuronal types of the dorsal horn, and in positive motoneurons in the lumbar spinal cord, ipsilateral to the lesion. A similar increase was also demonstrable in spinal glial and endothelial cells. These findings are discussed in relation to the role of nitric oxide in hyperalgesia and neuronal regeneration or degeneration.